Production of grease from spent lubricant - Awang Omar Firdaus, Awang Ismail (2009)
This study was undertaken to examine the potential of spent lubricant as a medium to produce grease. Grease is a semi-solid colloidal dispersion of a thickener in a liquid lubricant matrix. Spent lubricant oils have significant potential as a base fluid and a substitute for mineral oil in grease formulations. The advantages of using products based on lubricant oils are their physical and chemical properties are close to that common grease production. Besides, this research allowing as optimizing the oil waste usage and reduce the environmental problem towards waste disposal. This work focuses on the preparation methods, optimization of thickener components, and antioxidant additive for producing spent lube oil based grease. In greases, Li-fatty acid thickener having C12 to C18 chain lengths and different metal to fatty acid ratios were synthesized. The percentages of thickener were varied at 5%, 10%, 15% and 20%. The research also focuses on varying the mixing temperature during the saponification of grease. Four sets of reaction temperature were 150◦C, 170◦C, 200◦C, and 230◦C. Four types of grease properties or characteristic to be tested in this research were grease oxidation stability, penetration, dynamic viscosity, and dropping point. Results indicate that Li-thickener composition, fatty acid types and base oil content and reaction temperature significantly affect grease hardness, dynamic viscosity, oxidation, and dropping point. It has been observed that the physical and chemical properties of grease are largely based on the thickener fibre micro-structure.-Author-